The regional management of fisheries in European Western Waters. (January 2015) - Le Floc'h, Pascal; Murillas, Arantza; Aranda, Martin; Daurès, Fabienne; Fitzpatrick, Mike; Guyader, Olivier; Hatcher, Aaron; Macher, Claire; Marchal, Paul
Abstract: A survey of past and existing management measures applied to different fisheries in European Western Waters is analyzed as a typology of co-management between governments and stakeholders. Faced with increasing constraints on accessing fish stocks, management measures have evolved toward fishing rights individualization, limited access and various other specific measures. Restrictions on access have changed fishermen's behaviour in several significant ways. A comparative analysis, based on qualitative data collected through interviews and focus groups, is developed for fisheries from the following European countries: France, Ireland, Spain and the United Kingdom. Past and existing individual harvesting rights in the four countries are reviewed and compared.